Exercise-induced bronchodilation is not impacted by beta-adrenergic receptor blockade in males or females - Connor J. Doherty; Benjamin P. Thompson; Paige J. Rynne; Jou-Chung Chang; Sarah A. Angus; Armando J. Aguero; Sean L. Gartner; Paolo Dominelli (European Journal of Applied Physiology, 2026)

Numerical Analysis of Triaxial Tests for Interpreting Sample Stiffness with Existing Measurement Systems - W. Du; B. M. Lehane; J. P. Doherty; Z. Wang (Geotechnical and Geological Engineering, 2025)
This paper presents the first systematic numerical study employing a realistic elasto-plastic non-linear soil model to examine factors affecting the measurement of soil stiffness at low to intermediate strains in the triaxial apparatus. The study is motivated by the development of new image-based measurement techniques for triaxial testing. The results from numerical simulations are presented that quantify the influence on sample stiffness determination of three important features common to all triaxial tests, namely: the misalignment of the loading direction and the top of the sample (and indirectly bedding errors), the use of fixed or free load cell connections and the effect of system compliance. The analyses compare data obtained using four different instrumentation systems employed for axial strain measurement with overall predicted deformations and elemental response of a typical sand sample. The paper highlights some of the significant errors that can occur in standard triaxial tests and makes recommendations to assist more accurate determinations of sample stiffness. It is also shown numerically that, despite sample and test imperfections, the common approach of averaging data from at least two strain gauges located on a triaxial sample’s middle third can lead to reasonable inference of a soil’s elemental Youngs modulus.

Field measurements of steelhead trout Oncorhynchus mykiss distribution, swimming behavior and response to water current exposure in a sea cage - M. Chambers; M. Doherty; M. Coogan; C. Rillahan; J. DeCew; P. Lader; W.H. Howell (Aquaculture, 2025)

Corrigendum to “Preliminary assessment of potential pile tip damage and extrusion buckling” [Ocean Eng. 275 (1 May 2023) 114071] - Juliano A. Nietiedt; Mark F. Randolph; Christophe Gaudin; James P. Doherty (Ocean Engineering, 2024)

Organic acid preservation of cereal grains improves grain quality, growth performance, and intestinal health of post-weaned pigs - Shane Maher; Torres Sweeney; Dillon P. Kiernan; Marion T. Ryan; Vivian Gath; Stafford Vigors; Kathryn Ruth Connolly; John V. O’Doherty (Animal Feed Science and Technology, 2024)

Corrigendum to “Relationships between lateral and rotational load transfer stiffnesses and soil modulus for the elastic response of monopiles” [Comput. Geotech. 137 (2021) 104256] - Xiao Wan; James P. Doherty; Mark F. Randolph (Computers and Geotechnics, 2023)

P16-33: Identifying and characterizing toxicity liabilities of pharmaceuticals using ToxProfiler: A blinded case study with the ITLF consortium - B. Ter Braak; L. Wolters; K. Elbertse; M. Beilmann; H. Boonen; A. Doherty; F. Van Goethem; P. Hewitt; J. Hornberg; J. Koch; S. Kusterman; J. Lyon; et al. (Toxicology Letters, 2023)

Preliminary assessment of potential pile tip damage and extrusion buckling - Juliano A. Nietiedt; Mark F. Randolph; Christophe Gaudin; James P. Doherty (Ocean Engineering, 2023)

Effects of meteorological and land surface modeling uncertainty on errors in winegrape ET calculated with SIMS - Conor T. Doherty; Lee F. Johnson; John Volk; Meagan S. Mauter; Nicolas Bambach; Andrew J. McElrone; Joseph G. Alfieri; Lawrence E. Hipps; John H. Prueger; Sebastian J. Castro; Maria Mar Alsina; William P. Kustas; et al. (Irrigation Science, 2022)
Characterization of model errors is important when applying satellite-driven evapotranspiration (ET) models to water resource management problems. This study examines how uncertainty in meteorological forcing data and land surface modeling propagate through to errors in final ET data calculated using the Satellite Irrigation Management Support (SIMS) model, a computationally efficient ET model driven with satellite surface reflectance values. The model is applied to three instrumented winegrape vineyards over the 2017–2020 time period and the spatial and temporal variation in errors are analyzed. We illustrate how meteorological data inputs can introduce biases that vary in space and at seasonal timescales, but that can persist from year to year. We also observe that errors in SIMS estimates of land surface conductance can have a particularly strong dependence on time of year. Overall, meteorological inputs introduced RMSE of 0.33–0.65 mm/day (7–27%) across sites, while SIMS introduced RMSE of 0.55–0.83 mm/day (19–24%). The relative error contribution from meteorological inputs versus SIMS varied across sites; errors from SIMS were larger at one site, errors from meteorological inputs were larger at a second site, and the error contributions were of equal magnitude at the third site. The similar magnitude of error contributions is significant given that many satellite-driven ET models differ in their approaches to estimating land surface conductance, but often rely on similar or identical meteorological forcing data. The finding is particularly notable given that SIMS makes assumptions about the land surface (no soil evaporation or plant water stress) that do not always hold in practice. The results of this study show that improving SIMS by eliminating these assumptions would result in meteorological inputs dominating the error budget of the model on the whole. This finding underscores the need for further work on characterizing spatial uncertainty in the meteorological forcing of ET.

Microbiome assembly in thawing permafrost and its feedbacks to climate - Jessica G. Ernakovich; Robyn A. Barbato; Virginia I. Rich; Christina Schädel; Rebecca E. Hewitt; Stacey J. Doherty; Emily D. Whalen; Benjamin W. Abbott; Jiri Barta; Christina Biasi; Chris L. Chabot; Jenni Hultman; et al. (Global Change Biology, 2022)
The physical and chemical changes that accompany permafrost thaw directly influence the microbial communities that mediate the decomposition of formerly frozen organic matter, leading to uncertainty in permafrost–climate feedbacks. Although changes to microbial metabolism and community structure are documented following thaw, the generality of post‐thaw assembly patterns across permafrost soils of the world remains uncertain, limiting our ability to predict biogeochemistry and microbial community responses to climate change. Based on our review of the Arctic microbiome, permafrost microbiology, and community ecology, we propose that Assembly Theory provides a framework to better understand thaw‐mediated microbiome changes and the implications for community function and climate feedbacks. This framework posits that the prevalence of deterministic or stochastic processes indicates whether the community is well‐suited to thrive in changing environmental conditions. We predict that on a short timescale and following high‐disturbance thaw (e.g., thermokarst), stochasticity dominates post‐thaw microbiome assembly, suggesting that functional predictions will be aided by detailed information about the microbiome. At a longer timescale and lower‐intensity disturbance (e.g., active layer deepening), deterministic processes likely dominate, making environmental parameters sufficient for predicting function. We propose that the contribution of stochastic and deterministic processes to post‐thaw microbiome assembly depends on the characteristics of the thaw disturbance, as well as characteristics of the microbial community, such as the ecological and phylogenetic breadth of functional guilds, their functional redundancy, and biotic interactions. These propagate across space and time, potentially providing a means for predicting the microbial forcing of greenhouse gas feedbacks to global climate change.

Mismatches in scale between highly mobile marine megafauna and marine protected areas - Melinda G. Conners; Nicholas B. Sisson; Pierre D. Agamboue; Philip W. Atkinson; Alastair M. M. Baylis; Scott R. Benson; Barbara A. Block; Steven J. Bograd; Pablo Bordino; W. D. Bowen; Paul Brickle; Ignacio M. Bruno; et al. (Frontiers in Marine Science, 2022)
Marine protected areas (MPAs), particularly large MPAs, are increasing in number and size around the globe in part to facilitate the conservation of marine megafauna under the assumption that large-scale MPAs better align with vagile life histories; however, this alignment is not well established. Using a global tracking dataset from 36 species across five taxa, chosen to reflect the span of home range size in highly mobile marine megafauna, we show most MPAs are too small to encompass complete home ranges of most species. Based on size alone, 40% of existing MPAs could encompass the home ranges of the smallest ranged species, while only < 1% of existing MPAs could encompass those of the largest ranged species. Further, where home ranges and MPAs overlapped in real geographic space, MPAs encompassed < 5% of core areas used by all species. Despite most home ranges of mobile marine megafauna being much larger than existing MPAs, we demonstrate how benefits from MPAs are still likely to accrue by targeting seasonal aggregations and critical life history stages and through other management techniques.

Use of Exposomic Methods Incorporating Sensors in Environmental Epidemiology - Brett T. Doherty; Jeremy P. Koelmel; Elizabeth Z. Lin; Megan E. Romano; Krystal J. Godri Pollitt (Current Environmental Health Reports, 2021)

Systems biology analysis identifies molecular determinants of chemotherapy-induced diarrhoea - Andreas U. Lindner; Alexa J. Resler; Steven Carberry; Kasia Oficjalska; Orna Bacon; Chun Seng Lee; Abdurehman Choudhry; John P. Burke; Kieran Sheahan; Mattia Cremona; Bryan T Hennessy; Deborah McNamara; et al. (Journal of Molecular Medicine, 2020)

Seasonal changes in basking shark vertical space use in the north-east Atlantic - P. D. Doherty; J. M. Baxter; B. J. Godley; R. T. Graham; G. Hall; J. Hall; L. A. Hawkes; S. M. Henderson; L. Johnson; C. Speedie; M. J. Witt (Marine Biology, 2019)
Mobile marine species can exhibit vast movements both horizontally and vertically. Spatial analysis of vertical movements may help improve an understanding of the processes that influence space use. Previously, vertical space use of basking sharks ( Cetorhinus maximus ) in the north-east Atlantic described movements largely within waters of the continental shelf during summer and autumn months, with few records of detailed vertical behaviour during winter. We use archival satellite telemetry data from 32 basking sharks (12 females, 6 males, and 14 of unknown sex measuring 4–5 m ( n = 6), 5–6 m ( n = 10), 6–7 m ( n = 7), 7–8 m ( n = 8), and 8–9 m ( n = 1) estimated total length) tracked over 4 years (2012–2015). The satellite tags provided depth and temperature data for a cumulative 4489 days (mean 140 ± 97 days per shark, range 10–292 days) to describe vertical space use and thermal range of basking sharks in the north-east Atlantic. Basking sharks exhibit seasonality in vertical space use, revealing repeated ‘yo-yo’ movement behaviour with periods of occupancy at depths greater than 1000 m in late winter/early spring. Describing seasonal vertical space use in marine megavertebrates can increase knowledge of movements throughout their environment including physiological and morphological constraints to movement, nutrient transfer, and overlap with anthropogenic threats to inform future conservation strategies.

Novel transcriptional responses to heat revealed by turning up the heat at night - Dmitry O. Grinevich; Jigar S. Desai; Kevin P. Stroup; Jiaqi Duan; Erin Slabaugh; Colleen J. Doherty (Plant Molecular Biology, 2019)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Molecular detection of kobuviruses in livestock in Northern Ireland and the Republic of Ireland - P. J. Collins; Michael J. McMenamy; Julie McClintock; Paula Lagan-Tregaskis; Lorna McCabe; Simon Doherty; Helen O’Shea; Michael Welsh; John McKillen (Archives of Virology, 2017)

Large‐scale, multidirectional larval connectivity among coral reef fish populations in the Great Barrier Reef Marine Park - David H. Williamson; Hugo B. Harrison; Glenn R. Almany; Michael L. Berumen; Michael Bode; Mary C. Bonin; Severine Choukroun; Peter J. Doherty; Ashley J. Frisch; Pablo Saenz‐Agudelo; Geoffrey P. Jones (Molecular Ecology, 2016)
Larval dispersal is the key process by which populations of most marine fishes and invertebrates are connected and replenished. Advances in larval tagging and genetics have enhanced our capacity to track larval dispersal, assess scales of population connectivity, and quantify larval exchange among no‐take marine reserves and fished areas. Recent studies have found that reserves can be a significant source of recruits for populations up to 40 km away, but the scale and direction of larval connectivity across larger seascapes remain unknown. Here, we apply genetic parentage analysis to investigate larval dispersal patterns for two exploited coral reef groupers ( Plectropomus maculatus and Plectropomus leopardus ) within and among three clusters of reefs separated by 60–220 km within the Great Barrier Reef Marine Park, Australia. A total of 69 juvenile P. maculatus and 17 juvenile P. leopardus (representing 6% and 9% of the total juveniles sampled, respectively) were genetically assigned to parent individuals on reefs within the study area. We identified both short‐distance larval dispersal within regions (200 m to 50 km) and long‐distance, multidirectional dispersal of up to ~250 km among regions. Dispersal strength declined significantly with distance, with best‐fit dispersal kernels estimating median dispersal distances of ~110 km for P. maculatus and ~190 km for P. leopardus . Larval exchange among reefs demonstrates that established reserves form a highly connected network and contribute larvae for the replenishment of fished reefs at multiple spatial scales. Our findings highlight the potential for long‐distance dispersal in an important group of reef fishes, and provide further evidence that effectively protected reserves can yield recruitment and sustainability benefits for exploited fish populations.

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

Hydrologic Regimes Revealed Bundles and Tradeoffs Among Six Wetland Services - James M. Doherty; Jeffrey F. Miller; Stephanie G. Prellwitz; Anita M. Thompson; Steven P. Loheide; Joy B. Zedler (Ecosystems, 2014)

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

Genome-wide association study of endometrial cancer in E2C2 - Immaculata De Vivo; Jennifer Prescott; Veronica Wendy Setiawan; Sara H. Olson; Nicolas Wentzensen; John Attia; Amanda Black; Louise Brinton; Chu Chen; Constance Chen; Linda S. Cook; Marta Crous-Bou; et al. (Human Genetics, 2014)

Cigarette smoking and risk of ovarian cancer: a pooled analysis of 21 case–control studies - Mette T. Faber; Susanne K. Kjær; Christian Dehlendorff; Jenny Chang-Claude; Klaus K. Andersen; Estrid Høgdall; Penelope M. Webb; Susan J. Jordan; Mary Anne Rossing; Jennifer A. Doherty; Galina Lurie; Pamela J. Thompson; et al. (Cancer Causes & Control, 2013)

Comparison of model building and selection strategies - Paul F. Doherty; Gary C. White; Kenneth P. Burnham (Journal of Ornithology, 2012)

The Shaft Capacity of Displacement Piles in Clay: A State of the Art Review - P. Doherty; K. Gavin (Geotechnical and Geological Engineering, 2011)

Long-term effects of hydropower installations and associated river regulation on River Shannon eel populations: mitigation and management - T. K. McCarthy; P. Frankiewicz; P. Cullen; M. Blaszkowski; W. O’Connor; D. Doherty (Hydrobiologia, 2008)

Delivery of cancer genetics services: The Royal Marsden telephone clinic model - S. Shanley; K. Myhill; R. Doherty; A. Ardern-Jones; S. Hall; C. Vince; S. Thomas; P. Aspinall; R. Eeles (Familial Cancer, 2007)

Linkage mapping of the locus for inherited ovine arthrogryposis (IOA) to sheep Chromosome 5 - Angela M. Murphy; David E. MacHugh; Stephen D.E. Park; Erik Scraggs; Chris S. Haley; David J. Lynn; Maurice P. Boland; Michael L. Doherty (Mammalian Genome, 2007)

Turbulent mixing and mesoscale distributions of late‐stage fish larvae on the NW Shelf of Western Australia - M. G. MEEKAN; J. H. CARLETON; C. R. STEINBERG; A. D. MCKINNON; R. BRINKMAN; P. J. DOHERTY; A. HALFORD; S. DUGGAN; L. MASON (Fisheries Oceanography, 2006)
Light traps were deployed to describe vertical and cross‐shelf distributions of late‐stage larval fishes during five cruises in each of the 1997/98 and 1998/99 summers in the region of the Gulf of Exmouth on the southern North West Shelf of Western Australia. At each light trap station on a cross‐shelf transect we measured water temperature, salinity and chlorophyll a and used vertical plankton tows to estimate zooplankton biomass and copepod abundance. Current meters were deployed on moorings near the transect and the data used to model flows and mixing on the NW Shelf and in the Gulf. The majority of reef, pelagic and baitfish larvae (81, 83 and 66% respectively) were collected at only two stations that marked the boundary between stratified waters offshore and well‐mixed water within the Gulf. Most baitfishes (primarily Spratelloides spp.) were captured by traps deployed near the seabed, while reef fishes (mostly pomacentrids, lethrinids and siganids) and pelagic species (mostly scombrids and carangids) were captured in traps deployed near surface. Catch composition varied between summers with 64% of baitfishes collected in the first summer, while the majority of reef and pelagic fishes (81 and 80% respectively) were captured in the second summer. Modelling of circulation showed that the velocity of tidal currents was enhanced by constriction of flow between NW Cape and South Muiron Island and by shallowing of the shelf. Flood‐tide intrusions of water allowed the thermocline to move up the continental shelf, upwelling cool nutrient‐rich water that was then mixed throughout the entire water column at stations in the mouth of the Gulf. This upwelling and mixing resulted in higher chlorophyll a concentrations and copepod abundances either as a result of local in situ growth or advection/aggregation processes, and may account for the great abundances of late‐stage fish larvae in the mouth of the Gulf.

AGAGE Observations of Methyl Bromide and Methyl Chloride at Mace Head, Ireland, and Cape Grim, Tasmania, 1998–2001 - P. G. Simmonds; R. G. Derwent; A. J. Manning; P. J. Fraser; P. B. Krummel; S. O'Doherty; R. G. Prinn; D. M. Cunnold; B. R. Miller; H. J. Wang; D. B. Ryall; L. W. Porter; et al. (Journal of Atmospheric Chemistry, 2004)

Subcutaneous Administration of a Recombinant Vaccinia Virus Vaccine Expressing Multiple Envelopes of HIV-1 - K. S. Slobod; T. D. Lockey; N. Howlett; R. V. Srinivas; S. D. Rencher; P. J. Freiden; P. C. Doherty; J. L. Hurwitz (European Journal of Clinical Microbiology & Infectious Diseases, 2004)

Regional Sources of Methyl Chloride, Chloroform and Dichloromethane Identified from AGAGE Observations at Cape Grim, Tasmania, 1998–2000 - M. L. Cox; G. A. Sturrock; P. J. Fraser; S. T. Siems; P. B. Krummel; S. O'Doherty (Journal of Atmospheric Chemistry, 2003)

Characterisation of the expression of a novel constitutive maize promoter in transgenic wheat and maize - S. Rasco-Gaunt; D. Liu; C. Li; A. Doherty; K. Hagemann; A. Riley; T. Thompson; C. Brunkan; M. Mitchell; K. Lowe; E. Krebbers; P. Lazzeri; et al. (Plant Cell Reports, 2003)

Zooplankton community structure and water flow in the lee of Helix Reef (Great Barrier Reef, Australia) - Carleton J.; Brinkman R.; Doherty P. (Marine Biology, 2001)

Dual X-ray absorptiometry detects disease- and treatment-related alterations of bone density in prostate cancer patients - Gillian L. Smith; Alan P. Doherty; Linda M. Banks; Jane Dutton; Iain W. Hanham; Timothy J. Christmas; Richard J. Epstein (Clinical & Experimental Metastasis, 2000)

Hydroxyl Radical Concentrations Estimated from Measurements of Trichloroethylene during the EASE/ACSOE Campaign at Mace Head, Ireland during July 1996 - R. G. Derwent; N. Carslaw; P. G. Simmonds; M. Bassford; S. O'Doherty; D. B. Ryall; M. J. Pilling; A. C. Lewis; J. B. McQuaid (Journal of Atmospheric Chemistry, 1999)

A population of wheat and tritordeum transformants showing a high degree of marker gene stability and heritability - M. E. Cannell; A. Doherty; P. A. Lazzeri; P. Barcelo (Theoretical and Applied Genetics, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Acute Toxicity of Potassium to the Adult Zebra Mussel Dreissena polymorpha - P. J. Wildridge; R. G. Werner; F. G. Doherty; E. F. Neuhauser (Archives of Environmental Contamination and Toxicology, 1998)

Tropical zooplankton in the highly-enclosed lagoon of Taiaro Atoll (Tuamotu Archipelago, French Polynesia) - J. H. Carleton; P. J. Doherty (Coral Reefs, 1998)

Objectives and background to the 1994 Franco-Australian expedition to Taiaro Atoll (Tuamotu Archipelago, French Polynesia) - R. Galzin; S. Planes; M. Adjeroud; C. Chauvet; P. J. Doherty; J. Poupin (Coral Reefs, 1998)

Replenishment of fish populations in the enclosed lagoon of Taiaro Atoll: (Tuamotu Archipelago, French Polynesia) evidence from eggs and larvae - J. M. Leis; T. Trnski; P. J. Doherty; V. Dufour (Coral Reefs, 1998)

Genetic relationships of the colour morphs of Acanthochromis polyacanthus (Pomacentridae) on the northern Great Barrier Reef - S. Planes; P. J. Doherty (Marine Biology, 1997)

Hypotensive effects of hydroxylamine in intact anesthetized dogs and cats - Robert Kruszyna; Harriet Kruszyna; Patricia A. Doherty; Roger P. Smith (Archives of Toxicology, 1984)